2020
DOI: 10.1016/j.resmer.2020.100768
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory support in patients with COVID-19 (outside intensive care unit). A position paper of the Respiratory Support and Chronic Care Group of the French Society of Respiratory Diseases

Abstract: With first cases noted towards the end of 2019 in China, COVID-19 infection was rapidly become a devastating pandemic. Even if most patients present with a mild to moderate form of the disease, the estimated prevalence of COVID-19-related severe acute respiratory failure (ARF) is 15-20% and 2-12% needed intubation and mechanical ventilation. In addition to mechanical ventilation some other techniques of respiratory support could be used in some forms of COVID-19 related ARF. This position paper of the Respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“… 15 , 16 , 17 Most guidelines recommend NIV in patients with SARS-CoV-2 infection as a “default” option when oxygen therapy or constant positive airway pressure (CPAP) are not sufficient to improve patient's status, provided that appropriate personal protective equipment is available. 10 , 14 , 18 , 19 Its indications in this context therefore remain restricted to situations in which access to invasive mechanical ventilation is limited, in patients not eligible to ICU admission, or in patients with underlying respiratory disease or previously undergoing long-term NIV in which NIV cessation could worsen even more their condition and for whom the results of the present study apply as well. 14 , 20 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 15 , 16 , 17 Most guidelines recommend NIV in patients with SARS-CoV-2 infection as a “default” option when oxygen therapy or constant positive airway pressure (CPAP) are not sufficient to improve patient's status, provided that appropriate personal protective equipment is available. 10 , 14 , 18 , 19 Its indications in this context therefore remain restricted to situations in which access to invasive mechanical ventilation is limited, in patients not eligible to ICU admission, or in patients with underlying respiratory disease or previously undergoing long-term NIV in which NIV cessation could worsen even more their condition and for whom the results of the present study apply as well. 14 , 20 …”
Section: Discussionmentioning
confidence: 97%
“… 10 , 14 , 18 , 19 Its indications in this context therefore remain restricted to situations in which access to invasive mechanical ventilation is limited, in patients not eligible to ICU admission, or in patients with underlying respiratory disease or previously undergoing long-term NIV in which NIV cessation could worsen even more their condition and for whom the results of the present study apply as well. 14 , 20 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Concerns have been raised that PAP use is an aerosol generating procedure at this time, per CDC 5 . It is reported that non-invasive ventilation is considered an aerosol generating procedure which could increase risk of pathogen exposure and infection and has been recommended for non-vented masks to be used if available 6 . Recently, PAP machine performance was tested and completely sealed systems resulted in worse maximal inspiratory pressures, inspiratory effort to trigger the machine, tidal volume, and work of breathing 7 .…”
Section: Discussionmentioning
confidence: 99%
“… Normal with by-pass leak using a T-connector as recommended to reduce the risk of droplet aerosolization. 6 …”
mentioning
confidence: 99%